2001
DOI: 10.1038/sj.onc.1204746
|View full text |Cite
|
Sign up to set email alerts
|

Chk2 tumour suppressor protein in human spermatogenesis and testicular germ-cell tumours

Abstract: Chk2 is a transducer of DNA damage signals and a tumour suppressor whose germ-line mutations predispose to diverse tumour types. Unlike its downstream targets such as the p53 tumour suppressor, the expression patterns of Chk2 in tissues and tumours remain unknown. As DNA breaks occur commonly during gametogenesis, and p53 is wild-type and overexpressed in testicular cancer, we examined abundance and localisation of the Chk2 protein during normal development of human testes, and at various stages of germ-cell t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 28 publications
3
55
0
1
Order By: Relevance
“…A previous study of protein expression in normal human tissues and cell lines has indicated that CHK2 protein is relatively stable and it is expressed at similar levels in all phases of the cell cycle, as well as in quiescent and terminally differentiated cells. 39 In our study, we demonstrated that CHK2 protein levels were relatively similar in different types of malignant lymphomas, including both low and highly proliferative neoplasms such as CLL and blastoid MCL or LCL, indicating that CHK2 protein expression in these tumors is independent of the proliferative activity and the histologic type of the tumors. CHK2 protein expression levels were similar in malignant lymphomas and reactive lymphoid tissues, whereas quiescent peripheral blood lymphocytes had very low or absent protein expression.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…A previous study of protein expression in normal human tissues and cell lines has indicated that CHK2 protein is relatively stable and it is expressed at similar levels in all phases of the cell cycle, as well as in quiescent and terminally differentiated cells. 39 In our study, we demonstrated that CHK2 protein levels were relatively similar in different types of malignant lymphomas, including both low and highly proliferative neoplasms such as CLL and blastoid MCL or LCL, indicating that CHK2 protein expression in these tumors is independent of the proliferative activity and the histologic type of the tumors. CHK2 protein expression levels were similar in malignant lymphomas and reactive lymphoid tissues, whereas quiescent peripheral blood lymphocytes had very low or absent protein expression.…”
Section: Discussionmentioning
confidence: 75%
“…Several CHK2 mutations have been shown to facilitate destabilization and increased degradation of CHK2 protein in human tumors. 26,[39][40][41] However, no mutations, deletions, or hypermethylation of the promoter region were identified in any of these cases. On the other hand, mRNA levels were relatively similar in cases with low and normal protein expression, indicating that other mechanisms may regulate the stability of the protein in these lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation, but not mutation, of Chk2 in sporadic breast cancer in some respects resembles p16 INK4a wherein loss of expression, rather than mutation, occurs in a subset of cancers (Herman et al, 1995). It will clearly be of interest to evaluate Chk2 expression in other common cancers, and Chk2 has recently been shown to be down-regulated in a subset of testicular germ-cell tumours (Bartkova et al, 2001). The authors of this study emphasized the importance of studying promoter silencing in cancers with reduced Chk2 expression and in the present report we have addressed the possibility of methylation-dependent silencing.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, unlike Plk1, it is not clear that Chk2 functions are required in a normal cell cycle, rather than being called into play only after genotoxic damage. In human testes, Chk2 protein is more abundant in spermatogonia (mitotic division), than in spermatocytes (meiotic division), indicating a possible mitotic role for Chk2 (55).…”
Section: Chk2mentioning
confidence: 99%